Penerapan Biaya Diferensial Dalam Pengambilan Keputusan Membeli Atau Memproduksi Sendiri Outlet Pisang Goreng Nugget - Agung Pangestu, Putra; Nusantoro, Jawoto; Hendri, Nedi (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to analyze the application of management accounting information at Pisang Goreng Nugget Outlets in making decisions to buy or produce their own banana nugget raw materials. The type of research used in this study is qualitative, the research method used is a quantitative descriptive method in which this method describes or describes the application of management accounting information so that it can be used as a short-term decision-making tool at the Metro City Fried Banana Nugget Outlet. Data collection techniques in conducting this research, using observation and interview data collection methods. The results of this study the use of differential accounting information is very useful for the management of the Metro City Fried Banana Nugget Outlet in obtaining the information needed to be able to compare which decision is more profitable between buying or producing bugget banana raw materials yourself.